Hysteretic model development and seismic response of unbonded post-tensioned precast CFT segmental bridge columns. - Chou, Chung-Che
The study investigated the cyclic behavior of unbonded, post-tensioned, precast concrete filled tube segmental bridge columns by loading each specimen twice. Moreover, a stiffness degrading flag shaped (SDFS) hysteretic model was developed based on self centering and stiffness degrading behaviors. The proposed model overcomes the deficiency of cyclic behavior prediction using a FS model, which self centers with fixed elastic and inelastic stiffnesses. Experimental and analytical results showed that (1) deformation capabilities of the column under the first and second cyclic tests were similar; however, energy dissipation capacities significantly differed from each other, and (2) the SDFS model predicted the cyclic response of the column better than the FS model. Inelastic time history analyses were performed to demonstrate the dynamic response variability of a single degree of freedom (SDOF) system using both models. A paremetric study, performed on SDOF systems subjected to eight historical earthquakes, showed that increased displacement ductility demand was significant for structures with a low period and low to medium yield strength ratio and reduced displacement ductility demand in these systems was effectively attained by increasing energy dissipation capacity.
Keywords: Cyclic test; Stiffness degrading flag shaped model; Time history analysis